2011
DOI: 10.1249/mss.0b013e31820abc5a
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent-Sprint Performance and Muscle Glycogen after 30 h of Sleep Deprivation

Abstract: Sleep loss and associated reductions in muscle glycogen and perceptual stress reduced sprint performance and slowed pacing strategies during intermittent-sprint exercise for male team-sport athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 36 publications
3
97
1
1
Order By: Relevance
“…The effects of sleep loss (sleep restriction and sleep deprivation) on exercise performance, and physiological and cognitive responses to exercise have been extensively reviewed [25]. Some studies have showed that extensive and total sleep deprivation negatively affects physical recovery among team sport athletes [114,115], which suggests the significance of sleep debt to athletic performance. Such results should be interpreted with caution as sleep deprivation is rarely total after a soccer match.…”
Section: Sleep Deprivation and Post-match Fatiguementioning
confidence: 99%
See 2 more Smart Citations
“…The effects of sleep loss (sleep restriction and sleep deprivation) on exercise performance, and physiological and cognitive responses to exercise have been extensively reviewed [25]. Some studies have showed that extensive and total sleep deprivation negatively affects physical recovery among team sport athletes [114,115], which suggests the significance of sleep debt to athletic performance. Such results should be interpreted with caution as sleep deprivation is rarely total after a soccer match.…”
Section: Sleep Deprivation and Post-match Fatiguementioning
confidence: 99%
“…Consequently, it is relevant to examine the potential detrimental effects of sleep deprivation on muscle glycogen repletion among players. Skein et al [114] determined the effects of extensive sleep loss (i.e. 30 h of sleep deprivation) on consecutive-day intermittent-sprint performance and muscle glycogen content among team-sport athletes.…”
Section: Glycogen Repletionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the effects of carbohydrate ingestion on indices of sleep quality and quantity are limited and provide contradictory results [11]. However, to counteract the potential decreased rate of muscle glycogen resynthesis among soccer players exposed to sleep deprivation [87], a preventive strategy may be to ensure additional carbohydrate is consumed in these circumstances [88]. Apart from quantity, the glycemic index of carbohydrate is also important to consider.…”
Section: Sleep and Nutritional Strategiesmentioning
confidence: 99%
“…1 Given that people spend about one-third of their lives asleep, sleep has substantial functions for development, daily functioning, and health. 2 Perhaps no daytime behavior has been associated more closely with improved sleep than exercise.…”
mentioning
confidence: 99%